The effectiveness of strategies to change organisational culture to improve healthcare performance - Parmelli, Elena (2011)
BACKGROUND: Organisational culture is an anthropological metaphor used to inform research and consultancy and to explain organisational environments. Great emphasis has been placed during the last years on the need to change organisational culture in order to pursue effective improvement of healthcare performance. However, the precise nature of organisational culture in healthcare policy often remains underspecified and the desirability and feasibility of strategies to be adopted has been called into question. OBJECTIVES: To determine the effectiveness of strategies to change organisational culture in order to improve healthcare performance. To examine the effectiveness of these strategies according to different patterns of organisational culture. SEARCH METHODS: We searched the following electronic databases for primary studies: The Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, CINAHL, Sociological Abstracts, Web of Knowledge, PsycINFO, Business and Management, EThOS, Index to Theses, Intute, HMIC, SIGLE, and Scopus until October 2009. The Database of Abstracts of Reviews of Effectiveness (DARE) was searched for related reviews. We also searched the reference lists of all papers and relevant reviews identified, and we contacted experts in the field for advice on further potential studies. SELECTION CRITERIA: We considered randomised controlled trials (RCTs) or well designed quasi-experimental studies, controlled clinical trials (CCTs), controlled before and after studies (CBAs) and interrupted time series analyses (ITS) meeting the quality criteria used by the Cochrane Effective Practice and Organisation of Care Group (EPOC). Studies should be set in any type of healthcare organisation in which strategies to change organisational culture in order to improve healthcare performance were applied. Our main outcomes were objective measures of professional performance and patient outcome. DATA COLLECTION AND ANALYSIS: At least two review authors independently applied the criteria for inclusion and exclusion criteria to scan titles and abstracts and then to screen the full reports of selected citations. At each stage results were compared and discrepancies solved through discussion. MAIN RESULTS: The search strategy yielded 4239 records. After the full text assessment, no studies met the quality criteria used by the EPOC Group and evaluated the effectiveness of strategies to change organisational culture to improve healthcare performance. AUTHORS’ CONCLUSIONS: It is not possible to draw any conclusions about the effectiveness of strategies to change organisational culture because we found no studies that fulfilled the methodological criteria for this review. Research efforts should focus on strengthening the evidence about the effectiveness of methods to change organisational culture to improve health care performance.